The effect of financial stability, ineffective monitoring and auditor opinion on financial statement fraud (Empirical Study on Multinational Companies Listed on the IDX ) - Sinaga, Judith; Siagian, Valentine (12th International Scholars Conference 2025, 2026)
This study aims to determine the effect of financial stability, ineffective monitoring, and auditor opinion on financial statement fraud. The population in this study are multinational companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2020 period. This research is a quantitative method using secondary data form company’s annual reports and audited financial statements. The sampling technique used purposive sampling with a total of 140 samples. The data analysis method in this study using descriptive statistical analysis, logistic regression test, and hypothesis test with the help of IBM SPSS 26 software. The results of the analysis show that simultaneously financial stability, ineffective monitoring, and auditor opinion have a significant effect on financial statement fraud. Partially, financial stability has a positive and significant effect on financial statement fraud, while ineffective monitoring and auditor opinion have no significant effect on financial statement fraud. The use of ineffective monitoring and auditor opinion variables has not been able to prove any indications of fraud in the financial statements therefore further researchers can use other variables as factors that can affect financial statement fraud.